(untitled) (Journal of Global Accounting, 2023)
The objective of this study is to ascertain the effect of Board Diversity on Financial Performance of quoted Natural resources companies in Nigeria. The specific objectives are to ascertain the effect or otherwise of Foreign Directorship and Board Size on Return on Assets, Return on Equity and Tobin’s Q of quoted Natural resources companies in Nigeria from 2008-2017. Ex-post facto research design was used for this study. Secondary data were sourced from the publications of Nigeria Stock Exchange. Inferential statistics of the hypotheses were carried out with the aid of E-view 9.0 statistical software using Co-efficient of correlation and Multivariate Panel Least Square Regression analysis. Findings of this study showed Board Diversity has a significant positive effect on Return on Assets and Tobin’s Q; a significant negative effect on Returns on Equity at 5% level of significance respectively. It was recommended among others that Natural Resources firms should have a suitable and diverse board size designed so as to guarantee diversity of experience without conceding independence, accountability, compatibility, more knowledge, integrity and enthusiasm of members to attend meetings.